Optimal Age for Preventive Replacement of A System with GPP Repair Process - Chien, Yu-Hung; Chiang, Chung-Piao (International Journal of Engineering and Technology, 2018)
A new and more general type of repair, called the â€˜GPP repairâ€™, is applied in this study, which is defined base on the Generalized Polya Process and it is more close to practical situations than the â€˜minimal repairâ€™. Under the GPP repair assumption, the future reliability performance of a system becomes worse and worse as the number of system failures occurred in the past increases. Cost model is developed and the corresponding optimal replacement age is derived such that the long-run expected cost rate is minimized. Structural properties of the optimal replacement age for the GPP repairable system are obtained.Â